Tuberculosis in Ukrainian War Refugees and Migrants in the Czech Republic and Slovakia: A Molecular Epidemiological Study - Dohál, Matúš; Dvořáková, Věra; Šperková, Miluše; Pinková, Martina; Ghodousi, Arash; Omrani, Maryam; Porvazník, Igor; Rasmussen, Erik Michael; Škereňová, Mária; Krivošová, Michaela; Wallenfels, Jiří; Konstantynovska, Olha; et al. (Journal of epidemiology and global health, 2024)
BACKGROUND: The war in Ukraine has led to significant migration to neighboring countries, raising public health concerns. Notable tuberculosis (TB) incidence rates in Ukraine emphasize the immediate requirement to prioritize approaches that interrupt the spread and prevent new infections. METHODS: We conducted a prospective genomic surveillance study to assess migration's impact on TB epidemiology in the Czech Republic and Slovakia. Mycobacterium tuberculosis isolates from Ukrainian war refugees and migrants, collected from September 2021 to December 2022 were analyzed alongside 1574 isolates obtained from Ukraine, the Czech Republic, and Slovakia. RESULTS: Our study revealed alarming results, with historically the highest number of Ukrainian tuberculosis patients detected in the host countries. The increasing number of cases of multidrug-resistant TB, significantly linked with Beijing lineage 2.2.1 (p < 0.0001), also presents substantial obstacles to control endeavors. The genomic analysis identified the three highly related genomic clusters, indicating the recent TB transmission among migrant populations. The largest clusters comprised war refugees diagnosed in the Czech Republic, TB patients from various regions of Ukraine, and incarcerated individuals diagnosed with pulmonary TB specialized facility in the Kharkiv region, Ukraine, pointing to a national transmission sequence that has persisted for over 14 years. CONCLUSIONS: The data showed that most infections were likely the result of reactivation of latent disease or exposure to TB before migration rather than recent transmission occurring within the host country. However, close monitoring, appropriate treatment, careful surveillance, and social support are crucial in mitigating future risks, though there is currently no evidence of local transmission in EU countries.
Keywords: osoby s přechodným pobytem a migranti; Refugees; multirezistentní tuberkulóza; Humans; Tuberculosis; lidé středního věku; Transients and Migrants; Control of tuberculosis; Ukrajina; ozbrojené konflikty; Female; mladý dospělý; dospělí; Molecular Epidemiology; Migration; lidé; tuberkulóza; Tuberculosis, Multidrug-Resistant; Armed Conflicts; molekulární epidemiologie; Slovakia; Slovenská republika; Adult; ženské pohlaví; Male; Middle Aged; Mycobacterium tuberculosis; Adolescent; incidence; Incidence; Czech Republic; Young Adult; uprchlíci; Česká republika; mužské pohlaví; prospektivní studie; Ukraine; Tuberculosis epidemiology; mladiství; Prospective Studies